Modeling Postnatal Hearing Case Finding Within the Italian National Health System - Orzan, Eva; Pizzamiglio, Giulia; Marchi, Raffaella; Muzzi, Enrico; Monasta, Lorenzo; Torelli, Lucio; Feresin, Agnese (Frontiers in Pediatrics, 2021)
Objective: Despite the successful implementation of newborn hearing screening (NHS), a debate is emerging as to what should be the best means of enabling timely diagnosis and intervention for pre-schoolers with educationally significant sensorineural or conductive hearing impairment (HI) missed at the time of NHS or occurred after birth. Our study aims to document the proportion and characteristics of HIs diagnosed in children in need of audiologic assessment, in order to outline the optimization areas of an operational framework for auditory surveillance during preschool age. Method: The referral routes and outcomes of 730 audiological assessments performed in 3 years within the framework of the early hearing identification program in Trieste (Italy) were retrospectively analysed. Results: Among 570/595 completed evaluations, an HI was diagnosed in 114 children, 73,7% of which presenting an exclusively conductive HI due to middle ear effusion. HIs were found in 36/141 who failed NHS, and 60/385 pre-schoolers who were referred by the primary care paediatrician’s surveillance activity during well-child visits, with diagnostic yield of of 25,5% and 15,5%, respectively. Conclusion: On-going preschool surveillance in primary care setting integrated into a NHS program is feasible to conduct and may effectively identify HIs that missed NHS or were related with a risk factor. New triage instruments and protocols for immediate audiology referral could allow to obtain the diagnosis of educationally significant conductive and sensorineural HIs ahead of the development concern, and in the same way reduce patient mobility, thus optimizing timing efficiency and economic impact of the program.